2019
DOI: 10.1155/2019/7153109
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Superhydrophobic Polyvinyl Alcohol Sponge Using Water as the Only Solvent for Continuous Oil-Water Separation

Abstract: Few cases of hydrophobic materials synthesized in water have been reported. In this work, water, as the only solvent, is used to prepare a superhydrophobic sponge via a facile and environment-friendly route. The as-prepared sponge, namely silylated polyvinyl alcohol (PVA) sponge, exhibits superhydrophobic and superoleophilic characters. It has the static water contact angle (WCA) of 152 ± 1 and the static oil contact angle (OCA) of 0°, which can lead to excellent selectivity for oil-water separation. Besides, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…Generally, in this process the commercial sponge with the 3D structure can act as a template, while the functional groups on the surface of the sponge suggest that it can serve as a reactant with potential modifications, in order to alter the sponge's surface from hydrophilic to hydrophobic [39,64]. During the wet chemical reaction, the sponge can function either as a carrier or a reactant to participate in the chemical modification process [39,65].…”
Section: Methods For Commercial Melamine Sponge Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, in this process the commercial sponge with the 3D structure can act as a template, while the functional groups on the surface of the sponge suggest that it can serve as a reactant with potential modifications, in order to alter the sponge's surface from hydrophilic to hydrophobic [39,64]. During the wet chemical reaction, the sponge can function either as a carrier or a reactant to participate in the chemical modification process [39,65].…”
Section: Methods For Commercial Melamine Sponge Modificationmentioning
confidence: 99%
“…The as-prepared sponge was characterized by highly selective absorption of oil against water, high oil absorption capacity (up to 246 g/g), good recyclability, flexible compressibility, fire resistance and low density [85]. Therefore, this type of modified melamine sponge can be a promising oil-absorbent material, suitable for several applications, such as oil pollution control from water of solid surface and oil-water separation [64].…”
Section: Methods For Commercial Melamine Sponge Modificationmentioning
confidence: 99%
“…IKVAV )之间插入甘氨酸(Gly)和丝氨酸(Ser), 自组装形成的新型三维支架(RADA4GGSIKVAV, R-GSIK)可用作细胞培养的支架。与常规培养方法 相比,R-GSIK 更能促进细胞的黏附、繁殖和迁移, 在细胞治疗和神经元修复方面有广泛的应用前景 [115] 。Myriam 等 [116] 报道了可逆肽自组装,可用来调 控体内天然肽激素的活性。通过模仿高抗菌活性、 低毒性的抗菌肽 AMP 的特性,科研人员设计了具 有简单序列和结构的两亲性肽,表现出明显的抗菌 和抗肿瘤活性,并表明抗菌活性与设计分子自组形 成的形状有关 [117][118][119] 。结合肽自组装和酶催化,研 究人员还设计了能够在水溶液中自组装形成纳米带 的两亲性短肽,加入转谷氨酸酶(TGase)后,肽 溶液会形成刚性凝胶 [120] , 出血时血液中的凝血因子 被凝血酶转化为活性 TGase, 可用于止血 (图 10(a)) 。 多肽的衍生物,例如多肽与二酰亚胺类荧光分子的 共价结合形成的复合分子,可作为新型的细胞荧光 探针,用于细胞成像技术、跟踪和定位癌细胞等领 域 [121][122] (图 10(b))。 图 9 (a)SnS2 / Zn2SnO4 混合膜传感器的传感性能:人呼气、手掌出汗和婴儿尿布上的尿液及水滴计数 [74] , (b)基于 GOx 装载的 H / G4-PANI 水凝胶的葡萄糖传感器检测葡萄糖 [85] , (c)人体皮肤上的应变传感器阵列的实时响应 [83] Fig. 9 (a) SnS2 / Zn2SnO4 hybrid membrane sensor performance under different applications: human exhalation, palm sweating, urine and water droplets on baby diapers [74] ; (b) A glucose sensor based on GOx loaded H / G4-PANI hydrogel for detecting glucose [85] ; (c) Real-time response of strain sensor arrays on human skin [83] 2.4 其他 纳米仿生自组装材料的应用除了上述之外,还 可用在 CdSe 纳米棒组装阵列 [123][124] 以及 CdSe 纳米 棒的低成本无毒替代品 [125] , 在光伏器件领域也有很 好的应用。通过调节自组装材料和自组装条件,可 自组装形成特定的结构,如肽自组装纳米棒形成的 分形结构 [126] ,控制油水界面 CaCO3 晶体自组装形 貌 [127] 等。利用自组装形成的特定纳米结构(如纳 米管) 可作为模板生产银纳米线 [128] 。 在电化学方面, 在氧化还原过程中自组装金属纳米粒子表现出高活 性界面 [129][130] 。利用羟基氢键诱导自组装可以制备 疏水性能优异的高效、连续分离的油水分离材料, 如三元复合疏水聚氨酯海绵最高可吸收自身重量的 75 倍油品 [61] , 疏水化修饰后的聚乙烯醇绵在外加真 空系统辅助下可实现连续油水分离 [62] [120] , (b)用单光子激光扫描共聚焦显微镜观察 PC-3 细胞中的自 组装肽 [122] Fig. 10 (a) Rat liver hemostasis.…”
Section: 生物医疗unclassified
“…[58] ,(b)通过种子 Photo-PISA 制备负载 HRP 的温敏聚合物囊泡 [59] , (c)光诱导原位自组装合成聚合物纳米结构 [60] Fig. 7 (a) Schematic diagram of self-assembly and reassembly induced by light and metal ions [58] ; (b) Preparation of HRP-loaded temperature-sensitive polymer vesicles by seed Photo-PISA [59] ; (c) Light-induced in-situ self-assembly synthesis of polymer nanostructures [60] 图 8(a)采用溶胶-凝胶法水相制备疏水聚硅氧烷过程示意图 [61] , (b)羟基氢键诱导自组装制备三元复合物疏水聚氨 酯绵 PU/HEC/SiO2 过程示意图 [61] ,(c)羟基氢键诱导自组装疏水聚乙烯醇绵 PVA/SiO2 过程示意图 [62] Fig. 8 (a) Preparation of hydrophobic polysiloxane in aqueous phase by sol-gel method [61] ; (b) Schematic diagram of preparation of ternary composite hydrophobic polyurethane sponge PU/HEC/SiO2 by hydroxyl hydrogen bond induction self-assembly [61] ; (c) Schematic diagram of PVA / SiO2 with hydrophobicity induced by hydroxyl hydrogen bond [62] 此外,该团队以聚乙烯醇绵为基材,以 MTES 为修饰单体进行原位自组装合成了二元复合疏水聚 乙烯醇绵 [62] (图 8(a,c)) ,聚乙烯醇绵表面的羟基为 硅氧烷的原位聚合提供了活性位点,可以使聚甲基 硅氧烷对聚乙烯醇绵三维骨架孔道进行等型覆盖, 保持了聚乙烯绵的多孔结构,形成了稳定的二元复 合结构。等型覆盖降低了孔道表面自由能,增加了 表面粗糙度,修饰后的聚乙烯醇绵表面具有优异的 超疏水性能。…”
mentioning
confidence: 99%
“… 31 It is often used in the fields of tissue engineering, 32 adsorption materials, 33 , 34 and catalysts, 35 while there are only a few studies on superhydrophobic PVA-based sponges for oil/water separation. 36 39 For example, Chen et al prepared a superhydrophobic PVA sponge by using a facile and environment-friendly route, and the as-prepared PVA sponge showed long stability for continuous oil/water separation. 36 Sha et al reported that 3D superhydrophilic PVA-based composite sponges with high porosity can be used as efficient emulsion separation materials.…”
Section: Introductionmentioning
confidence: 99%